ARTIFICIAL INTELLIGENCE AND CRIME INVESTIGATION - Cuatrecasas Monforte, Carlota (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2023)
Bill Gates, the technologist par excellence of our era, uttered what is undoubtedly one of the best and most famous phrases reflecting the reality of the technological explosion we are experiencing today, which of course has its pros and cons: “The first rule of any technology used in a business is that automation applied to an efficient operation will magnify the efficiency. The second is that automation applied to an inefficient operation will magnify the inefficiency”. And such a statement, loaded with meaning and force, and applicable no doubt to the use of AI both in the private and public sector, should serve as a basis for any decision related to this technology. Because although many see it as a new potential saviour, the truth is that it has enormous potential to have an opposite effect – so it should be used with great caution.